Synonymous Mutations in rpsT Lead to Ribosomal Assembly Defects That Can Be Compensated by Mutations in fis and rpoA - Knöppel, Anna; Andersson, Dan I.; Näsvall, Joakim (Frontiers in Microbiology, 2020)
We previously described how four deleterious synonymous mutations in the Salmonella enterica rpsT gene (encoding ribosomal protein S20) result in low S20 levels that can be compensated by mutations that restore [S20]. Here, we have further studied the cause for the deleterious effects of S20 deficiency and found that the S20 mutants were also deficient in four other 30S proteins (S1, S2, S12, and S21), which is likely due to an assembly defect of the S20 deficient 30S subunits. We examined the compensatory effect by six additional mutations affecting the global regulator Fis and the C-terminal domain of the α subunit of RNA polymerase (encoded by rpoA). The fis and rpoA mutations restored the S20 levels, concomitantly restoring the assembly defect and the levels of S1, S2, S12, and S21. These results illustrate the complexity of compensatory evolution and how the negative effects of deleterious mutations can be suppressed by a multitude of mechanisms. Additionally, we found that the mutations in fis and rpoA caused reduced expression of other ribosomal components. Notably, some of the fis mutations and the rpoA mutation restored the fitness of the rpsT mutants to wild-type levels, although expression of other ribosomal components was reduced compared to wild-type. This finding raises new questions regarding the relation between ribosome concentration and growth rate.